Microplastic ingestion by periwinkle snail Littoraria scabra and mangrove crab Metopograpsus quadridentata in Pramuka Island, Jakarta Bay, Indonesia - Patria, Mufti Petala; Santoso, Clara Alverina; Tsabita, Nurma (Penerbit Universiti Kebangsaan Malaysia, 2020)
Microplastic has been known to contaminate our marine environment. This research aim was to determine the abundance of microplastic in mangrove periwinkle snail Littoraria scabra and mangrove crab Metopograpsus quadridentata in Pramuka Island, Jakarta Bay, Indonesia. Pramuka Island was chosen as the research site because this island is densely populated and received waste from Jakarta Bay. Samples of mangrove snails were taken by purposive random sampling method of 10 individuals with shell lengths ranging from 1.5 to 2.7 cm, and 9 individuals crab with circa 6 cm carapace wide were collected. Analysis of microplastic abundance was done by isolating microplastic in each sample. Isolation in the sample was done by dissolving tissue of animals in a 65% nitric acid (HNO3 ) solution for 24 h and sodium chloride (NaCl) was added to increase density of solution. Sample was observed under microscope. The results obtained 3 types of microplastic found in the body of snail (fiber, film, and fragment) and 4 types in crab (fiber, film, fragment, and granula). Fiber has the highest percentage in snail (66.89%) and crab (68.72%). The average of microplastic abundance were 86.88 particles/individual in snail and 327.56 particles/individual in crab, respectively. This result indicated that the coastal area of Pramuka Island has been polluted by the microplastics. There was positive correlation between microplastic abundance and the body weight of snail (r=0.9778), and body weight of crab (r=0.9193).